Mediating effect of respiratory symptoms on the association between residential distance and the quality of life among residents living near waste incineration plants in Dongguan, Southern China - Lizhou Zhang; Tippawan Liabsuetrakul (BMC Public Health)
Abstract Background Living near waste incineration plants (WIPs) may have adverse effects on health associated with quality of life (QOL) among local residents. This study was undertaken to measure the QOL of residents living near WIPs in China, identify the association between residential distance from the WIPs and QOL, and assess the mediating effect of respiratory symptoms on the association between residential distance and QOL. Methods A cross-sectional study was conducted in communities surrounding three municipal WIPs in Dongguan, China. The QOL using the WHOQOL-BREF and respiratory symptoms using the Medical Research Council Questionnaire (MRCQ) on Respiratory Symptoms were measured in 881 residents (454 living 3 km of their local WIP vs. 427 living 3–8 km from the WIP). Differences in respiratory symptoms and QOL in two separate items and four domains were analyzed. The associations of distance with respiratory symptoms and QOL were evaluated by multiple linear regression and logistic regression, respectively. Mediating effect of respiratory symptoms on the association between distance and QOL were tested using mediation analysis. Results Compared with the 3–8 km group, residents in the 0–3 km group had significantly lower scores in the physical health domain (β= − 2.02, p = 0.027), social relationships domain (β= − 2.47, p = 0.016) and environment domain (β= − 3.55, p < 0.001). There were no significant associations between distance and psychological domain, overall QOL, and satisfaction with health after adjusting for other variables. Residents in the 0–3 km group were more likely to report respiratory symptoms than residents in the 3–8 km group (OR = 1.46, 95%CI 1.09–1.96, p = 0.011). Respiratory symptoms had a significant effect on physical health (β= − 7.48, p < 0.001), social relationships (β= − 5.02, p < 0.001) and environment domains (β= − 7.28, p < 0.001). Respiratory symptoms fully mediated the association of residential distance on physical health (31.7%), and partially mediated the associations of residential distance on social relationships (18.8%) and environment domains (17.3%). Conclusions Residential distance from a WIP was significantly associated with QOL, and the association between residential distance and QOL was mediated by respiratory symptoms. Future longitudinal studies on adverse respiratory health effects of exposure to WIP emissions are required using objective assessments.